Enhancement of Clathrate Hydrate Formation Kinetics Using Carbon-Based Material Promotion - Song, Yuan-Mei; Liang, Ru-Quan; Wang, Fei; Shi, Jian-Hui; Zhang, Deng-Bo; Yang, Liu (Frontiers in Chemistry, 2020)
Although the hydrate-based technology has been considered as a safe and environmental-friendly approach for the gas storage and transportation in recent decades, there are still inherent problems during hydrates production, such as the long induction time, slow formation kinetics and limited hydrates storage capacity. Attempts to resolve these issues have resulted in the development of various kinetic promoters, among which the carbon-based materials become one of the most attractive promoters owing to their unique promotion effect. Herein, the promotion results of the bulk wetting carbon materials in forms of packed bed, the carbon particles in suspensions and the nano-carbon materials in nanofluid are collected from the published literature. Meanwhile, the promotion mechanisms and influencing factors of the carbon-based promoters are discussed. The purpose of this mini review is to summarize the recent advances and highlight the prospects and future challenges of the carbon-based materials employed in the hydrate productions.